Development of Selection Method for Genetic Potential and Adjusment of Nutritional Requirement to Stimulate Gene Expression of Local Meat Chicken - Yaman, M. Aman; Dasrul, Dasrul; Zulfan, Zulfan (Universitas Syiah Kuala, 2009)
This study aimed to evaluate the genetic potential of local meat chickens (LMC) to get the candidate of parent stock through the development of the selection method applied, as well as economical and practical approach and adjusment of nutritional requirement, especially protein and energy balance. Research was divided into 2 groups, where the female and male parent was reared for 2 months and the offspring (F1) was reared for 4 months and selected. The parent was mated by the method of artificial insemination (AI). Method of selection was used on the orientation of the meat chicken production parameters with a positive correlation with the gene expression Diet treatments were formulated by optimal nutrition standards in order to drive maximum primary production of local meat chicken, contained 17, 19, and 21% of protein. The result showed that feeding diet with 19% protein can stimulate optimum growth and food conversion of ALPU male, whereas female growth LMC in line with the increasing availability of protein in the diet, wherein feeding 21% of protein result in optimal growth until age 4 months.